Nursing thought and history. Need for a philosophical and historical vertebration in Nursing - Amparo Nogales Espert (Universidad de Alicante, 2012)
Four topics are dealt with in this work: 1. Human beings as historical beings in constant evolution, since birth to the end of life. 2. History in Nursing and the role of Nursing in History. 3. Value of the knowledge on human beings, the key being care and a nurse self-realisation as a person. 4. Approach to a philosophy of Nursing as an impulse for reaching professional aims.